2013
DOI: 10.1095/biolreprod.112.105791
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Expression of Foxo1, but Not Foxo3, Is Conserved in Diverse Mammalian Species1

Abstract: The Foxos are key effectors of the PI3K/Akt signaling pathway and regulate diverse physiologic processes. Two of these factors, Foxo1 and Foxo3, serve specific roles in reproduction in the mouse. Foxo3 is required for suppression of primordial follicle activation in females, while Foxo1 regulates spermatogonial stem cell maintenance in males. In the mouse ovary, Foxo1 is highly expressed in somatic cells (but not in oocytes), suggesting an important functional role for Foxo1 in these cells. Given that inverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 53 publications
1
22
1
Order By: Relevance
“…Similarly, the overlapped expression of foxo3a and foxo3b in the brain was also observed in zebrafish, which was suggested to be critical for the development of the nervous system (Peng et al 2010, Xie et al 2011, and is in line with neuronal roles of FOXO3 reported in mammals (Fukunaga et al 2005, Fukunaga & Shioda 2009, Polter et al 2009, Renault et al 2009). In mammals, FOXO3 protein was detected predominantly in the oocytes of primordial and primary follicles in the ovary of mouse (John et al 2008, Tarnawa et al 2013 and pig , which was implicated in suppressing the primordial oocyte activation (Castrillon et al 2003. Similarly, our present study also identified strong immuno reactive Foxo3a and Foxo3b signals in germ cells in the ovary of the orange-spotted grouper.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, the overlapped expression of foxo3a and foxo3b in the brain was also observed in zebrafish, which was suggested to be critical for the development of the nervous system (Peng et al 2010, Xie et al 2011, and is in line with neuronal roles of FOXO3 reported in mammals (Fukunaga et al 2005, Fukunaga & Shioda 2009, Polter et al 2009, Renault et al 2009). In mammals, FOXO3 protein was detected predominantly in the oocytes of primordial and primary follicles in the ovary of mouse (John et al 2008, Tarnawa et al 2013 and pig , which was implicated in suppressing the primordial oocyte activation (Castrillon et al 2003. Similarly, our present study also identified strong immuno reactive Foxo3a and Foxo3b signals in germ cells in the ovary of the orange-spotted grouper.…”
Section: Discussionsupporting
confidence: 78%
“…Given that the vitellogenic oocytes in teleosts are arrested at Prophase I of meiosis (Lubzens et al 2010), it could be hypothesized that the nuclear Foxo3a and Foxo3b in the vitellogenic oocytes of the orange-spotted grouper presumably contribute to the inhibition of Prophase I progression, which awaits further study. Mammalian FOXO3 proteins have been shown to be undetectable (John et al 2008, Tarnawa et al 2013 or barely detectable (Reddy et al 2005, Matsuda et al 2011 in the granulosa cells of healthy follicles. By contrast, prominent immunoreactive Foxo3a and Foxo3b signals were identified in follicular (presumably granulosa) cells surrounding the oocytes in the orange-spotted grouper.…”
Section: Discussionmentioning
confidence: 99%
“…7 A). Foxo1 expression was used as a convenient marker of undifferentiated spermatogonia (Goertz et al 2011, Tarnawa et al 2013). Immunostaining and counts revealed normal numbers of undifferentiated spermatogonia in Vasa-Cre; Rheb f /− testes at all time points (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Foxo1 is specifically expressed in undifferentiated spermatogonia, and the three Foxos together regulate multiple steps of spermatogenesis including stem cell maintenance and differentiation (Goertz et al 2011, Tarnawa et al 2013). Pten is also required for spermatogenesis; its inactivation with the germline-specific Vasa-Cre (Gallardo et al 2007a) results in severe defects in spermatogonial maintenance and differentiation, at least in part through Foxo1 (Goertz et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several studies reported how the various components of this pathway have sex-specific roles. Foxo1 is specifically expressed in undifferentiated spermatogonia, and the three Foxos together regulate multiple steps of spermatogenesis comprising stem cell maintenance and differentiation (Figure 3) (Goertz et al , 2011; Tarnawa et al , 2013). Pten is also required for spermatogenesis and its inactivation with the germ line-specific Vasa-Cre (Tg(Ddx4-cre)1Dcas) (Gallardo et al , 2007) results in severe defects in spermatogonial maintenance and differentiation, in part through Foxo1 (Goertz et al , 2011).…”
Section: Mtor and Testicular Cellsmentioning
confidence: 99%